2015
DOI: 10.1523/jneurosci.1537-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Neurotransmission in the Posterior Insular Cortex Is Altered in Preclinical Models of Neuropathic Pain: Key Role of Muscarinic M2 Receptors in Donepezil-Induced Antinociception

Abstract: Neuropathic pain is one of the most debilitating pain conditions, yet no therapeutic strategy has been really effective for its treatment. Hence, a better understanding of its pathophysiological mechanisms is necessary to identify new pharmacological targets. Here, we report important metabolic variations in brain areas involved in pain processing in a rat model of oxaliplatin-induced neuropathy using HRMAS 1 H-NMR spectroscopy. An increased concentration of choline has been evidenced in the posterior insular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Consequently, the level of acetylcholine (ACh) may be lower in the pain-related brain regions, which was observed in the poster insular cortex of oxaliplatin-treated rats. 7 The basal release of ACh was significantly lower in rats with partial ligation of the sciatic nerve. 34 Our data further showed that the expression levels of both M1 and M2 were decreased in the VTA, PFC, and striatum, suggesting that the regulation of the mAChRs system by the reward system was downregulated under the chronic pain condition.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Consequently, the level of acetylcholine (ACh) may be lower in the pain-related brain regions, which was observed in the poster insular cortex of oxaliplatin-treated rats. 7 The basal release of ACh was significantly lower in rats with partial ligation of the sciatic nerve. 34 Our data further showed that the expression levels of both M1 and M2 were decreased in the VTA, PFC, and striatum, suggesting that the regulation of the mAChRs system by the reward system was downregulated under the chronic pain condition.…”
Section: Discussionmentioning
confidence: 89%
“…3 Different subtypes of mAChRs are expressed in the sensory pathway, including at the terminal of the primary afferent nerve, 4,5 the spinal cord, 6 and the superspinal cord brain regions. 7 Both genetic and pharmacologic approaches have been used to study the involvement of mAChRs in the modulation of nociception. 8 Significant antinociceptive effects were observed after the administration of cholinesterase inhibitors or agonists of mAChRs in basic research studies.…”
mentioning
confidence: 99%
“…The insular mainly accepts pain perception and it can relieve pain (Brooks and Tracey, 2007). In addition, more than 50% of hemodialysis patients experience pain, approximately 69% of hemodialysis patients present with joint pain, and almost all of the patients with hemodialysis therapy exhibit non-specific symptoms, such as cramps or headaches (Davison, 2003), resulting from alterations in the concentration of metabolic substances, such as dopamine receptors in the insular (Ferrier et al, 2015). Therefore, decreased thalamo-insular connection may be an important mechanism of pain in hemodialysis patients, suggesting that insular is a key brain region in pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the level of acetylcholine (ACh) may be lower in the pain-related brain regions, which was observed in the poster insular cortex of oxaliplatintreated rats. 7 The basal release of ACh was significantly lower in rats with partial ligation of the sciatic nerve. 34 Our data further showed that the expression levels of both M1 and M2 were decreased in the VTA, PFC, and striatum, suggesting that the regulation of the mAChRs system by the reward system was downregulated under the chronic pain condition.…”
Section: Downregulation Of Machrs Under the Chronic Pain Conditionmentioning
confidence: 89%